Older Age and Longer Epilepsy Duration Do Not Predict Worse Seizure Reduction Outcome after Vagus Nerve Stimulation - Chrastina, Jan; Kocvarova, Jitka; Novak, Zdenek; Dolezalova, Irena; Svoboda, Michal; Brazdil, Milan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Introduction We analyzed the results of vagus nerve stimulation (VNS) on older patients and patients with long-lasting epilepsy and included severely intellectually disabled patients.Patients and Methods A total of 103 adults with VNS implanted from 2005 to 2014 were studied. The responder rates, that is, the percentage of VNS patients who responded to VNS, classified as seizure reduction ≥ 50% (50R) and seizure reduction ≥ 90% (90R), were compared in defined age groups (< 40 and ≥ 40 years, and < 50 and ≥ 50 years) and epilepsy duration groups (< 20 and ≥ 20 years, < 30 and ≥ 30 years, and < 40 and ≥ 40 years) at the 1-year follow-up visit and the last follow-up visit (at least 2 years after surgery). The age distributions and responder rates were also studied in patients with an intellectual disability.Results The analysis did not confirm a significantly lower 50R or 90R rate in patients ≥ 40, ≥ 50, or ≥ 60 years when compared with their younger counterparts, but the 50R rate increase during follow-up care was the lowest in patients ≥ 50 and ≥ 60 years. The highest percentage of patients with an intellectual disability in the group < 40 years of age did not adversely affect the 50R rate. Longer epilepsy duration was not confirmed as a negative predictor of VNS outcome. There was a significantly higher 50R rate in patients with epilepsy duration ≥ 20 years (at the last follow-up visit) and a higher 90R rate in patients with epilepsy duration ≥ 30 years (at the 1-year follow-up visit). The increase in the 50R rate during follow-up care was lower in patients with epilepsy durations ≥ 30 and ≥ 40 years.Conclusions The study did not find worse VNS outcomes, as defined by the 50R or 90R rate, in older adult patients or in patients with a longer epilepsy duration. The increasing stimulation effect over time is less marked in older patients and in patients with longer epilepsy duration.
Keywords: epilepsy; vagus nerve stimulation; seizures reduction; responder